Satisfaction and motivation of homeowners towards green homes - Tan, Teck-Hong * (Springer, 2013)
Whilst green homes have been constructed by housing developers in Malaysia, developers should determine how satisfied homeowners are with their green homes. This paper first reviews data from a survey to determine the satisfaction level of homeowners towards their residence in terms of green features in Iskandar Malaysia. Next, factor analysis is carried out to identify benefits that motivate households to own green homes, and then followed by logistic regression analysis to determine the effects of motivators on housing satisfaction. Results show that homeowners are most satisfied with the green features of high ceiling, North–South orientation, double-glazed panel glass doors and windows, solar panel system and landscaped parks with facilities. Rain water harvesting system and low-flow water fixtures, on the other hand, are the least satisfied green features among homeowners. Four motivators are found that describe households’ belief about green homes: ‘Financial Incentives’, ‘Healthy and Sustainable Environment’, ‘Energy Efficiency’ and ‘Livability’. The findings also demonstrated that the extent of housing satisfaction may depend on what motivates homeowners to own green homes. It would seem that house buyers do not just demand a typical house to stay in but also sustainable houses that do not compromise the environment.